Epigenome‐wide three‐way interaction study identifies a complex pattern between TRIM27, KIAA0226, and smoking associated with overall survival of early‐stage NSCLC. Issue 3 (7th January 2022) - Ji, Xinyu; Lin, Lijuan; Fan, Juanjuan; Li, Yi; Wei, Yongyue; Shen, Sipeng; Su, Li; Shafer, Andrea; Bjaanæs, Maria Moksnes; Karlsson, Anna; Planck, Maria; Staaf, Johan; et al.
Abstract : The interaction between DNA methylation of tripartite motif containing 27 (cg05293407 TRIM27 ) and smoking has previously been identified to reveal histologically heterogeneous effects of TRIM27 DNA methylation on early‐stage non‐small‐cell lung cancer (NSCLC) survival. However, to understand the complex mechanisms underlying NSCLC progression, we searched three‐way interactions. A two‐phase study was adopted to identify three‐way interactions in the form of pack‐year of smoking (number of cigarettes smoked per day × number of years smoked) × cg05293407 TRIM27  × epigenome‐wide DNA methylation CpG probe. Two CpG probes were identified with FDR‐ q  ≤ 0.05 in the discovery phase and P  ≤ 0.05 in the validation phase: cg00060500 KIAA0226 and cg17479956 EXT2 . Compared to a prediction model with only clinical information, the model added 42 significant three‐way interactions using a looser criterion (discovery: FDR‐ q  ≤ 0.10, validation: P  ≤ 0.05) had substantially improved the area under the receiver operating characteristic curve (AUC) of the prognostic prediction model for both 3‐year and 5‐year survival. Our research identified the complex interaction effects among multiple environment and epigenetic factors, and provided therapeutic target for NSCLC patients. Abstract : We performed a two‐phase designed epigenome‐wide three‐way gene‐smoking interaction study of NSCLC survival and identified two CpG probes (cg00060500 KIAA0226 and cg17479956 EXT2 ), together with pack‐year of smoking and cg05293407 TRIM27, exhibiting significant three‐way interaction effects. Meanwhile, these significant three‐way interactions substantially improved the area under the receiver operating characteristic curve (AUC) of the prognostic prediction model for both 3‐ and 5‐year survival.